A case of giant prostatic hyperplasia - Luke Wang; Paul Davis; Kevin McMillan (Asian Journal of Urology)
Benign prostatic hyperplasia (BPH) is one of the most common conditions experienced by aging males and a frequent cause of bladder outlet obstruction and macroscopic haematuria. Giant prostatic hyperplasia (GPH) is an extremely rare form of prostatic hyperplasia. We present a case of a patient with GPH of 800 mL. To our knowledge, this is the fourth largest prostatic hyperplasia ever reported in the literature.